Healthy Cities The Theory, Policy, and Practice of Value-Based Urban Planning - de Leeuw, Evelyne; Simos, Jean.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This forward-looking resource recasts the concept of healthy cities as not only a safe, pleasant, and green built environment, but also one that creates and sustains health by addressing social, economic, and political conditions. It describes collaborations between city planning and public health creating a contemporary concept of urban governance$1 (Ba democratically-informed process that embraces values like equity. Models, critiques, and global examples illustrate institutional change, community input, targeted assessment, and other means of addressing longstanding sources of urban health challenges. In these ambitious pages, healthy cities are rooted firmly in the worldwide movement toward balanced and sustainable urbanization, developed not to disguise or displace entrenched health and social problems, but to encourage and foster solutions. Included in the coverage: Towards healthy urban governance in the century of the city Healthy cities emerge: Toronto, Ottawa, Copenhagen The role of policy coalitions in understanding community participation in healthy cities projects Health impact assessment at the local level The logic of method for evaluating healthy cities Plus: extended reports on healthy cities and communities in North and Latin America, Africa, Europe, Asia, Oceania, and the Middle East Healthy Cities will interest and inspire community leaders, activists, politicians, and entrepreneurs working to improve health and well-being at the local level, as well as public health and urban development scholars and professionals. .s
Part I: Foundations and Historical Backdrop -- Introduction: Aims and Objectives of this Book -- Paleo-Epidemiology, Nomadism and Sedentism: Health and the City -- Urbanisation and Public Health -- Health in Canada in the 1970s and 1980s: Hotbed of Innovation -- Healthy Cities Emerge: Toronto - Ottawa - Copenhagen -- Healthy Cities Grow: Development of International, National, Regional, Linguistic Networks -- Eleven Qualities a City Should Strive to Provide (1986) -- Part II: Conceptual Framework and Analysis: Healthy Cities Working from a Joint Value Base -- From Movement to Maturity?- Africa - Anglophone -- Africa - Francophone -- Africa - Maghreb -- Arabic -- Central and South America -- North America -- Europe -- South-East Asia -- Asia-Pacific -- Oceania -- Wrap-Up: Values and Governance for Urban Health -- Part III: The Analysis Continues: Thematic Priorities -- The Role of the Community and Policy Coalitions -- Greening the City -- Environments for Health -- From Urban Projects to Healthy City Policies -- Futuring for Healthy Mega-Cities -- Methodological Reflections on Generating Evidence for Healthy Cities -- Health and Social Impact Assessment for Urban Health -- Conclusion: A Critical Appraisal at the Movement's 25th Birthday.
Keywords: Medicine; Health promotion; Urban geography; Sociology, Urban; Medicine & Public Health; Health Promotion and Disease Prevention; Urban Geography / Urbanism (inc. megacities, cities, towns).; Urban Studies/Sociology.